(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Overweight and obesity are major risk factors for a number of chronic diseases, including diabetes, cardiovascular diseases and hypertension. Once considered a problem only in high income countries, overweight and obesity are now dramatically on the rise in low and middle-income countries, particularly in urban settings. A person with a BMI of 30 or more is generally considered obese. A person with a BMI equal to or more than 25 is considered overweight. Medodhatuvridhi causes Snigdhata of Shareera, Udara-parshvavridhi, Kasa, Shwasa, Hikka and Daurgandhya of Shareera. The Medovaha Srotas moola means the organs closely related to the functions of Medodhatu or the important sites related to beginning or ending of the channels of Medodhatu. The Acharya (Charaka, Sushruta and Vagbhata) considered Vrikka as Moola of Medovaha Srotas and also considered Vapavahana, Kati and Mamsa as second Moola respectively. The present study was conducted on 30 clinically diagnosed patients of ’Medoroga’ (Obesity). The patients of ‘Medoroga’ (Obesity) were randomly divided into three groups of 10 patients in each. In Group A, 10 patients were treated with ‘Navakaguggulu’ 2 tab (each tab. of 500mg) three times a day with lukewarm water for 30 days. In Group B, 10 patients were treated with ‘Triphala Kwatha’ 50ml two times a day (morning and evening) for 30 days and in Group C, 10 patients were treated with ‘Navakaguggulu’ 2 tab (each tab. of 500 mg) three times a day with lukewarm water and ‘Triphala Kwatha’ 50ml two times a day (morning and evening) for 30 days. After completion of trial, Group C has shown the best result followed by Group A and B while in lab parameters Group A has shown highly significant result only in Triglyceride level. Similarly Group Cprovided better results in majority of the parameters.